As gestações subsequentes em mulheres que tiveram sífilis na gestação - Hebmuller, Marjorie Garlow (2014)
Importance: Many efforts have ocurred in identify risk factors and causes of congenital syphilis (CS) persistence along years, and in many cases, the repetition of the condition in the same woman. In Rio Grande do Sul, there are no studies about the reincidence of CS, its causes and outcomes. Objectives: To investigate the next pregnancies in women who already had syphilis in a previous pregnancy. Methods: The study sample were women with obstetrical events ocurred in São Lucas Hospital (SLH) between may 1997 and december 2004. We included all patients with syphilis before or during pregnancy who had newborns, stillborns or abortions with CS, as patients correctly treated for syphilis before delivery and that had newborns without syphilis. The CS cases were defined according to the Brazilian Ministry of Health (appendix 1). The follow-up period for the subsequent pregnancies was until december 2011. The data were analised in program Epi Info 3.4, using the χ² test or Fisher exact test for associations, and Mann-Whitney-Wilcoxon test for comparison of medians. The level of significance was set at p < 0,05. Results: We identified 450 women with positive tests for syphilis that had at least one obstetrical event in SLH between may 1997 and december 2004, within 166 had at least one more obstetrical event in the same hospital until december 2011.Cases of CS were 82% in the initial events and 68,5% in the subsequent s (OR 2,09, CI95% 1,3-3,3). Within patients with CS in the initial event, 72% had at least one more pregnancy with CS, against 56,6% of patiens without CS in the initial event(OR 1,97, CI95% 0,9-4,4). Conclusions: Many cases of CS with adverse outcomes ocurred in the subsequent pregnancies, although less than in the initial events. It is suspected that more uninfected newborns may have been defined as cases of congenital syphilis in subsequent pregnancies, because of the lack of records of maternal history and the absence or inadequacy of prenatal care. It is important to increase surveillance on women who have already had one pregnancy with syphilis.